Mimogonellus dreybrodti sp. n., a new cave-inhabiting Osoriinae from Laos (Coleoptera: Staphylinidae) - Yin, Zi-Wei; Steiner, Helmut (Zootaxa, 2017)
A new osoriine species, Mimogonellus dreybrodti Yin & Steiner, sp. n., collected from a cave in Houaphanh Province, Laos, is described and illustrated. This represents the third Mimogonellus species in Asia, and the first in the genus known to inhabit a cave environment.